The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/ta.0000000000003272
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcomes 6 to 12 months after interpersonal violence: A multicenter cohort study

Abstract: Violence continues to be a significant public health burden, but little is known about the long-term outcomes of these patients. Our goal was to determine the impact of violence-related trauma on long-term functional and psychosocial outcomes. METHODS:We identified trauma patients with moderate to severe injuries (Injury Severity Score, ≥9) treated at one of three level 1 trauma centers. These patients were asked to complete a survey over the phone between 6 and 12 months after injury evaluating both functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The majority of studies were conducted prospectively ( n = 52) [ 2 , 29 – 40 , 50 52 , 54 , 56 59 , 61 72 , 77 , 78 , 80 , 86 , 130 , 133 , 136 , 137 , 139 , 142 , 146 148 , 150 154 , 157 ] and in Germany ( n = 23) [ 35 , 39 , 41 – 44 , 51 , 52 , 57 , 62 65 , 71 , 73 75 , 79 , 80 , 83 , 86 , 152 , 154 ]. The average ISS in studies ranged from 9 to 57.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies were conducted prospectively ( n = 52) [ 2 , 29 – 40 , 50 52 , 54 , 56 59 , 61 72 , 77 , 78 , 80 , 86 , 130 , 133 , 136 , 137 , 139 , 142 , 146 148 , 150 154 , 157 ] and in Germany ( n = 23) [ 35 , 39 , 41 – 44 , 51 , 52 , 57 , 62 65 , 71 , 73 75 , 79 , 80 , 83 , 86 , 152 , 154 ]. The average ISS in studies ranged from 9 to 57.…”
Section: Resultsmentioning
confidence: 99%
“… Age : In 38 studies [ 2 , 29 – 49 , 133 , 134 , 136 , 138 , 140 , 144 – 151 , 153 , 154 , 157 ], the relationship between age and HRQoL was reported. The majority of those studies ( n = 24) found a significant correlation with age, mainly indicating that older age was an independent predictor of reduced HRQoL [ 2 , 29 , 31 , 33 , 35 37 , 41 , 42 , 44 , 133 , 134 , 136 , 138 , 145 147 , 149 , 153 , 154 , 157 ], disablement [ 46 , 152 ], and use of pain medication [ 149 ]. In some studies, the cut-off age for poor HRQoL was further specified: worse HRQoL was demonstrated in patients ≥ 55 [ 31 , 138 , 150 ], ≥ 60 [ 29 ], > 65 [ 139 , 148 , 154 ] and > 80 years [ 146 , 147 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairments in everyday daily living activities were found in approximately one third of patients with severe trauma; almost half did not return to work and was diagnosed with PTSD [197]. Up to 12 months post-injury approximately half of the patients reported daily pain [184,197].…”
Section: Trauma-specific Qol Questionnaire (T-qol)mentioning
confidence: 99%